(untitled) (Scientific journal of the Fergana State University, 2023)
The article considers the chronotopy of Uzbek literature. Its historical roots begin with folklore and ancient turcish writers,In the artistic perception of creativity, creators have been able to perceive the universe as a three dimentional world in its time, it is proved the possibility of division of chronotop into real and non-verbal types.